CODE SWITCHING IN SPICE! MAGAZINE : A Case Study in "Campus Life" Column in the SPICE! Magazine - Frimy Anisa Lestari, - (2011)
This research study entitled Code Switching in SPICE! Magazine, aims to investigate code switching and the readers' responses toward the use of code switching. This paper covers three major statements. First, it examines the types of code switching that occurred in the magazine. Second, it discusses the functions of code switching that occurred. The last, it investigates the readers' responses toward the use of code switching. The data were taken from 10 editorials of Campus Life column in SPICE! magazine. The method use in the present study is qualitative, which employs descriptive method. It uses some quantification to calculate the occurrences of code switching. This study involves 20 respondents and the writer uses questionnaires in order to get the readers' responses. The data were analyzed using the theory suggested by Poplack (1980) to identify the types of code switching. The functions of code switching were analyzed by using Koizol's theory (2000). In analyzing data, the writer uses several stages i.e. identify and underline the words, phrases, and sentences that contain code switching then categorize them by their types and functions in the tables, after calculating the occurrences of each type and function, the researcher interpreted the data, and the last was drawing some conclusions. There are several findings in this study. Based on the results the three types of code switching evidenced in the data are intrasentential, intersentential, and tag switching. However, intrasentential switching appears as the most frequent type. Then, there are only twelve functions of code switching occurring in the data. Those are personalization, reiteration, substitution, emphasis, clarification, untranslatability, mitigating message, interjection, parenthesis, aggravating message, quotation, and topic shift. Finally, the results also show the readers' attitude were positive toward the use of code switching. In conclusion, code switching is a phenomenon which is considered people in urban area tend to live in bilingual society so it is natural people switch their language into English.